Pengaruh Gaya Hidup dan Kemampuan Literasi Keuangan terhadap Perilaku Konsumtif Belanja Online - sardiyo sardiyo; Martini Martini (Politeknik Ganesha Medan, 2022)
This study analyzes student consumptive behavior associated with lifestyle and financial literacy during the covid-19 pandemic. The study was conducted at 15 of the best universities in the province of South Sumatra, the version of Webometrics 2021. This study used a survey method by distributing questionnaires to students online. Based on the results of hypothesis testing, the structural equation model testing each indicator of lifestyle variables has a significant positive effect on student consumptive behavior and financial literacy has a significant negative effect on student consumptive behavior. Simultaneously lifestyle and financial literacy affect the consumptive behavior of students in online shopping in South Sumatra Province during the covid-19 pandemic. Lifestyle increases a person's consumptive behavior, but financial literacy is able to suppress consumptive behavior for better decision-making to shop online.